Efficiency of phosphorus utilization in dairy operations - Joseph P. Harner; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2006)
Efficient utilization of nutrients is a must on modern dairies. Most of the phosphorus arriving at the dairy will either be found in purchased feedstuffs or commercial fertilizer used to raise grain and forage for the dairy. In general, those dairies that purchase all feeds are more efficient with phosphorus utilization than those that grow forage and grain. This is likely due to increased inefficiencies associ-ated with feeding and crop enterprises. Care-ful evaluation of diets to reduce feeding ex-cess phosphorus can reduce phosphorus excre-tion in the manure by as much as 50%. This not only reduces input costs, but also reduces the total cost of land application. The most efficient way to manage dairy farm nutrients is to develop a comprehensive nutrient manage-ment plan that includes both the cropping and animal enterprises. This plan will help pro-ducers predict phosphorus requirements of cattle and crops, and then allow the producer to control phosphorus inputs to meet the re-quirements.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Nutrient management; Phosphorus